Engaging chemistry educators through virtual roundtables: how the COVID-19 pandemic led to a community-wide initiative - M. Taylor Haynes; Justin M. Pratt; Matthew A. Cranswick; Kyle A. Grice; Chip Nataro; Sarah E. Shaner; Kari L. Stone; Meghan Porter; Jeffrey R. Raker (Discover Education, 2024)
Abstract Members of the Interactive Online Network of Inorganic Chemists (IONiC) report the development and sustained efforts to provide virtual professional development sessions: Supporting Learning with Interactive Teaching: a Hosted, Engaging Roundtable (SLiThEr). SLiThEr’s emerged from a community need at the start of the COVID-19 pandemic; since then, SLiThEr’s have become a standard event for the IONiC community. SLiThEr’s are real- time virtual community events, after which a recording of the SLiThEr is posted on the IONiC YouTube channel. In this paper, an overview of the structure, format, and emergence of SLiThEr’s is reported, followed by evaluation of SLiThEr offerings, a plan for future SLiThEr offerings, and a discussion of how SLiThEr’s impact teaching practice. Graphical Abstract